Decellularized biological matrices for the repair of rotator cuff lesions: a systematic review of preclinical in vivo studies - Codispoti, Giorgia; Carniato, Melania; Brogini, Silvia; Romanelli, Alessia; Martini, Lucia; Giavaresi, Gianluca; Tschon, Matilde (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Rotator cuff tears (RCTs), resulting from degeneration or trauma of the shoulder tendons, are one of the main causes of shoulder pain. In particular, massive RCTs represent the 40% of all injuries, require surgical treatment, and are characterized by poor clinical outcome and a high rate of failure. In recent years, the use of biological decellularized patch for augmentation procedures has received great interest owing to their excellent self-integration properties, improving healing and thus representing an innovative therapeutic option. However, the findings from clinical studies have emerged conflicting viewpoints regarding the benefits of this procedure, as an excessive tension load might compromise the integrity of the tendon-to-bone connection when the patch exhibits low elasticity or insufficient strength. This could prevent the healing process, leading to unpredictable results in the clinical practice. Methods: This systematic review was conducted following PRISMA guidelines across three databases (PubMed, Scopus, and Web of Knowledge) to underline the results obtained in preclinical studies involving animal models of RCT surgeries that utilized the biological decellularized matrix augmentation technique in the last 5 years. Results: Thirteen articles were included after screening, and the SYRCLE tools for assessing the risk of bias in in vivo studies was applied. Open-surgery techniques were conducted to create tendon defects or detachment in different animal models: rat (31%), rabbit (46%), dog (15%) and sheep (8%). Patches decellularized with not standardized protocols were used in 77% of studies, while commercially available matrices in 15%. Of the studies, 31% used allogenic patches, 61% xenogenic and 8% utilized both xenogenic and autologous ones. Conclusion: Overall, this review provides a comprehensive overview on the use of acellular patches and their effective therapeutic potential in RC repair at preclinical level with the aim to expand strategies and matrices available for surgeons.